Renovation Scheme of TCM100 Track Circuit - CHENG Lei (Chengshi guidao jiaotong yanjiu)
［Objective］ The initial application of TCM100 track circuit in China is in Shenzhen Metro Line 4 and Guangzhou Metro Line 8. During the early stage of equipment maintenance and repair, certain drawbacks in the power supply mode of the original TCM (track circuit module) group were detected. Replacing a single TCM module would affect the functions and displays of multiple track sections, and equipment failures occur frequently when TCM modules are replaced. Therefore, it is necessary to renovate the TCM100 track circuit. ［Method］ Based on a research of the TCM group in TCM100 track circuit, the defects existing in the "TCM Maintenance Manual" provided by Siemens AG and the power supply mode design of the TCM are pointed out, and a renovation scheme for the TCM100 track circuit is proposed. On the test track of a depot, the TCM replacement test on the renovated TCM100 track circuit is carried out. ［Result & Conclusion］ The renovation scheme of TCM100 track circuit is as follows: The single Wago terminal connected to the original positive electrode wire is replaced with three Wago terminals equipped with air switches, aiming to control the positive electrode power supply of the three TCM modules respectively, while the negative electrode power supply remains unchanged, thus realizing independent power supply of each module. The TCM module replacement test determines the optimal replacement method and proves the effectiveness of the track circuit renovation scheme.